1997
DOI: 10.1007/bf02750999
|View full text |Cite
|
Sign up to set email alerts
|

Frameless stereotactic guided neurosurgery: Clinical experience with an infrared based pointer device navigation system

Abstract: An infrared based frameless stereotactic navigation device (Easy Guide Neuro) was investigated for its clinical applicability, registration/application accuracy and limitations in a standard operating room set-up. In a five-month period 40 frameless stereotactic procedures (23 female, 17 male, mean age 46.4, yrs range 10-83) including 36 craniotomies and 4 spinal surgery procedures were performed. Image registration, data transfer and operation planning using skin fixed fiducials (between 5-10, mean 6.6) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
6

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(58 citation statements)
references
References 28 publications
5
47
0
6
Order By: Relevance
“…Even stereotactically directed navigation systems providing intraoperative radiologic resection guidance cannot solve the problem of defining tumor margins in radiologically well delineated tumor areas, because shift phenomena during resection of large tumor volumes occur. [25][26][27] Since the extent of resection determines survival in…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Even stereotactically directed navigation systems providing intraoperative radiologic resection guidance cannot solve the problem of defining tumor margins in radiologically well delineated tumor areas, because shift phenomena during resection of large tumor volumes occur. [25][26][27] Since the extent of resection determines survival in…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The advantages of the combined application of intraoperative CT and neuronavigation are the realization of neuronavigation without preoperative images and the possibility of recalibration with intraoperative images at any time during surgery. 5,6,8,9,13,16 Based on our results, there is a proven superiority in registration accuracy as compared to navigation using preoperative images. The detection, localization, and resection of residual tumor is another major advantage as is the intraoperative determination of tumor margins to achieve complete resection of intracerebral tumors.…”
Section: Discussionmentioning
confidence: 71%
“…2,[7][8][9] However, a major problem remains in the form of degradation of accuracy during frameless stereotactic neuronavigation due to brain and/or lesion shift. [12][13][14]16 To solve this problem, an intraoperative CT system was developed that can be connected to a navigation system to overcome the difficulty of working with preoperative images alone. 5,6,10,12 This amazing technical development enables the surgeon to work within a closed intraoperative network based on an intraoperative CT navigation system; the surgeon is a fixed, integrated part of that network.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, frameless stereotaxy in spinal surgery has been limited to a few procedures such as placement of pedicle screws 7 or as an adjunct to trans-oral approaches to the craniovertebral junction. 11 However, Roessler et al 12 found few clinical uses for such systems in spinal surgery since skin markers used for registration purposes resulted in excessive inaccuracy. In contrast, Foley and Smith 5 have described applications of interactive image-guided stereotaxis in the spine, and concluded that it was a valuable tool offering an increased margin of safety.…”
Section: Discussionmentioning
confidence: 99%